Bridging the Generational Gap between the Teachers and Students in the Utilization of Modern Technology in the Teaching Methods in Public Secondary Schools in Delta State - Urien, James (International Journal of Humanity and Social Sciences, 2024)
Purpose: The study focused on bridging the generational gap between the teachers and students in the utilization of modern technology in the teaching methods in secondary schools in Delta State. Two research questions were raised and two null hypotheses were formulated in the study. Methodology: The descriptive survey design was used. The population for this study comprised all public secondary school principals and teachers in Delta State. The sample for this study was 1533 and it is made up of 100 principals and 1433 teachers in Delta State public secondary schools selected from 12 Local Government Areas. Principals represented 50% while teachers represent 10% of the population. A self developed questionnaire was design titled “Bridging the Generational gap between the Teachers and Students in the Utilization of Modern Technology Questionnaire (BGTSUMTQ)”, validated and its reliability equally determined via a pilot study using test re-test reliability technique with a coefficient index of 0.96 was used. The research questions raised were answered using percentage for the study. The researcher employed descriptive statistic of mean scores and standard deviation to provide answers to the research questions while Pearson Product Moment Statistics was used to test the hypotheses at 0.05 level of significance. Findings: The findings revealed that there are factors that are associated with the utilization of modern technology in teaching methods in public secondary schools in Delta State. The use of technology in education is influenced by the following factors such as teacher factor, organizational factor, technological factor and student factor. It also showed that there are strategies to be adopted to improve teachers and students in the utilization of modern technology in teaching methods in public secondary schools in Delta State. Unique contribution to theory, practice and policy: Based on the findings, it therefore concluded that as a catalyst for massive change, technology has improved our existing understanding by assisting educators and students in making the most use of cutting-edge teaching techniques in Delta State public secondary schools.